Comparative study on lignocellulose liquefaction in water, ethanol, and water/ethanol mixture: Roles of ethanol and water. (15th July 2018) - Feng, Shanghuan; Wei, Rufei; Leitch, Mathew; Xu, Chunbao Charles
Abstract: This study aimed to investigate the roles of ethanol and water in the water/ethanol mixed solvent in liquefaction of lignocellulose biomass. To this end, an organosolv lignin, cellulose, cellulose/lignin (50:50, w/w) mixture and an acetone extracted white birch bark (EWBB) were comparatively liquefied in pure water, water/ethanol mixture (50:50, v/v) and pure ethanol at fixed condition (300 °C and 15 min). It was demonstrated that biomass liquefaction efficiency in three reaction media with respect to the bi-crude yield followed the order of water/ethanol mixed solvent » pure water > pure ethanol regardless of the feedstocks. Cellulose derived bio-crudes mainly contained esters, furfurals and furfurals derivatives, and carboxylic acid substantially existed in the bio-crude from cellulose liquefaction in water, while lignin derived bio-crude mainly contained aromatics, as expected. It was found that hot-compress water accelerated biomass depolymerization by hydrolyzing cellulose/hemi-cellulose, while on the other hand ethanol promoted lignin degradation by dissolving the de-polymerized lignin products and hence prevented the repolymerization of the reaction intermediates. In addition, the mixed ethanol-water solvent increased the permeation of the solvent into the lignocellulose biomass structure, and increased the solubility of liquefaction intermediates, hence contributing to a higher bio-crude yield in liquefaction of lignocellulose biomass. Highlights: Water/ethanol mixture was extremely efficient for lignocellulose liquefaction. Bio-crude from cellulose liquefaction in water/ethanol mixture was rich in furfural. Cellulose and bark derived bio-crudes have higher HHVs than the feeds. Hemicellulose was completely degraded during bark liquefaction. Ethanol presence with water increased solvent permeation into bark in liquefaction.